2013
DOI: 10.1152/ajpregu.00047.2013
|View full text |Cite
|
Sign up to set email alerts
|

Proton-facilitated ammonia excretion by ionocytes of medaka (Oryzias latipes) acclimated to seawater

Abstract: Liu ST, Tsung L, Horng JL, Lin LY. Proton-facilitated ammonia excretion by ionocytes of medaka (Oryzias latipes) acclimated to seawater. Am J Physiol Regul Integr Comp Physiol 305: R242-R251, 2013. First published May 15, 2013 doi:10.1152/ajpregu.00047.2013.-The proton-facilitated ammonia excretion is critical for a fish's ability to excrete ammonia in freshwater. However, it remains unclear whether that mechanism is also critical for ammonia excretion in seawater (SW). Using a scanning ion-selective electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 42 publications
4
34
0
Order By: Relevance
“…In medaka gills, mRNA levels of NHE2 and NHE3 were upregulated by acidified SW ( pH 7), suggesting that NHE was involved in acid secretion by SW-type ionocytes (Liu et al, 2016). Moreover, applying the scanning ion-selective electrode technique (SIET), Liu et al (2013Liu et al ( , 2016 have shown that treatment with an inhibitor of NHE suppressed both H + and Cl − secretion at ionocytes of SWacclimated medaka larvae. These findings indicate that NHE2 and NHE3 play critical roles in acid secretion, and that the acid secretion is linked to Cl − secretion in SW.…”
Section: Discussionmentioning
confidence: 99%
“…In medaka gills, mRNA levels of NHE2 and NHE3 were upregulated by acidified SW ( pH 7), suggesting that NHE was involved in acid secretion by SW-type ionocytes (Liu et al, 2016). Moreover, applying the scanning ion-selective electrode technique (SIET), Liu et al (2013Liu et al ( , 2016 have shown that treatment with an inhibitor of NHE suppressed both H + and Cl − secretion at ionocytes of SWacclimated medaka larvae. These findings indicate that NHE2 and NHE3 play critical roles in acid secretion, and that the acid secretion is linked to Cl − secretion in SW.…”
Section: Discussionmentioning
confidence: 99%
“…Keratinocyte is the most dominant cell type in body surface of fish. Several studies reported acid secretions in keratinocytes of zebrafish and medaka embryos (Wu et al, 2010 ; Liu et al, 2013 ; Furukawa et al, 2015 ). Although the ability of acid secretion in a single keratinocyteis far lower than that in a single HRC, the dominant keratinocytes still play a substantial role in acid secretion of the whole embryos.…”
Section: Discussionmentioning
confidence: 99%
“…In mangrove killifish ( Kryptolebias marmoratus ) 11 and Japanese eel 12 , NHE3 is present in the apical membrane of ionocytes. Recently, both NHE2 and NHE3 were identified in ionocytes of SW-acclimated medaka, in which they play a critical role in acid secretion 13 .…”
mentioning
confidence: 99%